Run healthy the runner's guide to injury prevention and treatment - Aguillard, Emmi 1991-
"The book offers the latest science-based guidelines for identifying, healing, and preventing the most common injuries experienced by road and trail runners. Readers will discover how the runner's body functions and responds to training, how to identify an injury, when rest is necessary, and when to seek professional treatment. Specific information on the feet and toes, ankles, knees, hips, and low back, including ways to keep these areas of the body safe and strong, is followed by coverage of specific conditions, including plantar fasciitis, Achilles tendinitis, shin splints, hamstring tendinitis and tendinopathy, and IT band syndrome"--Provided by publisher.
Exercise finder --Part I: the runner's body -- Understanding the body's tissues and their healing processes -- Navigating your treatment options -- Injuries to muscle and bone -- Soft tissue maintenance -- Part II: body regions -- Feet and toes -- Ankles -- Knees -- Hips --Low back -- Part III: Common conditions -- Plantar fasciitis -- Achilles tendinitis -- Shin splints -- Hamstring tendinitis and tendinopathy -- IT band syndrome -- Part IV: healthy training -- Principles of smart training -- Ideal running form -- Nutrition and fueling -- Alternative therapies and myth busting.
MSSalazar (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: Running injuries -- Prevention; Running injuries -- Treatment; Running -- Physiological aspects; SPORTS & RECREATION / Running & Jogging; HEALTH & FITNESS / Pain Management